Personal and interpersonal factors with the inclination to relapse - Asbah Razali (Faculty of Social and Political Science, Universitas Airlangga, 2017)
This study aims to identify a relationship between the personal factor of coping; the interpersonal factors of familial, friend, and societal support and the inclination to relapse. This study involves the participation of 169 former addicts that completed their treatment and rehabilitation period, by utilising four instruments: the Inventory of Drug-Taking Situations, (IDTS) by Annis and Martin (1985); Coping Strategy Inventory (COPE) by Carver and the Social Provisions Scale (SPS) by Russell and Cutrona (1984). The findings shows the inclination to relapse among former addicts are at a high level for the eight dimensions of the inclination to relapse. This means the participants of this study are at a high risk of relapsing into drug use. The descriptive analytical results towards the problem-focused coping, the emotional coping and evasive coping variables show it at a low level. This also applies to the analysis for the family, friend, and societal support variables. In addition, the correlation analysis for the variables of problem-focused, emotional, and evasive coping, selfefficacy, and family, friend, and societal support, shows a negative significant relationship with the inclination to relapse, with the relationship strength between r=-.60 and r=-.80. Therefore this study shows the importance of the personal and interpersonal factors in reducing the problem of inclination to relapse among former addicts that completed their treatment and rehabilitation period. In conclusion, results show the importance of the personal and interpersonal factor in the problem of inclination to relapse.